Optimalisasi Layanan Pengaduan Berbasis Website melalui Sosialisasi dan Pendampingan untuk Meningkatkan Responsivitas Pelayanan Publik di Kelurahan Dalung Kota Serang - Rani Sulastri Maulani; M. Dissha Najiah Al Yas'a; Nur Al Farizi; Dimas Rachmadi Ramdhan; Alina Trisalia Carla (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The implementation of a website-based public complaint service is part of the digital transformation of public services and supports the Electronic-Based Government System (SPBE). However, its utilization in Dalung Urban Village (Kelurahan), Cipocok Jaya District, Serang City, has not been optimal due to low public digital literacy, insufficient outreach, and limited staff capacity. This community service initiative aims to optimize the use of the complaint website through outreach, training, and mentoring. The study employs a Participatory Action Approach (PAA) with a qualitative descriptive method, utilizing observation, interviews, discussions, documentation, and activity evaluation. The results indicate an improvement in public understanding of how to use the website to submit complaints, as well as enhanced staff capability to manage reports more rapidly, transparently, and accountably. The program also fosters greater public participation in digital-based public services. The successful implementation of the complaint website depends not only on technological availability but also on human resource readiness, strengthened digital literacy, and sustained outreach. This mentoring model can be replicated in other urban villages to support the digital transformation of public services.